Consider the following function. g(x)=-sqrt(x+2)-5

Kaleigh Ayers 2022-09-14 Answered
Consider the following function.
g ( x ) = x + 2 5
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Karla Bautista
Answered 2022-09-15 Author has 16 answers
Given a function
g ( x ) = x + 2 5
Here we can Analyze that function g(x) is obtained by shifting the basic function downwards by 5 units.
And also function g(x) is obtained by shifting the basic function f(x) by 2 units left.
So if we take
f ( x ) = x
Shift f(x) 5 unit downward
f ( x ) 5 = x 5 f ( x + 2 ) 5 = x + 2 f ( x + 2 ) 5 = g ( x ) f ( x ) = x
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more